Long Term Efficacy of Antiviral Therapy: Mortality and Incidence of Hepatocellular Carcinoma - Hyun Woong Lee (The Korean Journal of Gastroenterology, 2019)
Multiple studies have shown that oral antiviral therapies reduced the incidence of hepatocellular carcinoma (HCC) and improved the survival of patients with chronic hepatitis B when compared with that of untreated patients. In particular, entecavir and tenofovir share the qualities of high efficacy in reducing the HBV DNA levels, and they have excellent tolerability and safety. These drugs modified the natural history of liver fibrosis, improve liver function, decrease the incidence of HCC, decrease the need for liver transplantation, and improve survival. Many studies have suggested that long-term antiviral therapy reduces the risk of HCC and liver cirrhosis in patients with chronic hepatitis. The mechanism of these drugs in reducing the risk of HCC is not clear. This article reviews the mechanisms of carcinogenic HBV by conducting a review of the literature on the efficacy of therapy for reducing the risk of HCC. A few recent articles have suggested that tenofovir offers advantages over entecavir in terms of HCC prevention, but these articles have the inherent limitations of observational data. No other head-to-head randomized trials exist. Further randomized studies would help provide stronger evidence of the association between the type of antiviral agent and the HCC outcomes. Only achieving complete viral eradication from the liver will truly decrease the mortality and incidence of HCC.